2012
DOI: 10.1007/s00586-012-2444-3
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid vertical and subaxial subluxation can be prevented by atlantoaxial posterior screw fixation

Abstract: Purpose Literature has described a risk for subsequent vertical subluxation (VS) and subaxial subluxation (SAS) following atlantoaxial subluxation in rheumatoid patients; however, the interaction of each subluxation and the radiographic findings for atlantoaxial fixation has not been described. The purpose of this study was to evaluate the effects of two different posterior atlantoaxial screw fixation on the development of subluxation in patients with rheumatoid atlantoaxial subluxation. Methods Between 1996 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Reduction is achieved sequentially by the pull strength of instruments via the posterior approach. Another advantage of the posterior approach is the realignment of the atlantoaxial joint, which can prevent subaxial degeneration due to misalignment of the cervical spine [26, 27]. In our study, only 1 patient achieved partial reduction, but this did not result in neurological deficits.…”
Section: Discussionmentioning
confidence: 63%
“…Reduction is achieved sequentially by the pull strength of instruments via the posterior approach. Another advantage of the posterior approach is the realignment of the atlantoaxial joint, which can prevent subaxial degeneration due to misalignment of the cervical spine [26, 27]. In our study, only 1 patient achieved partial reduction, but this did not result in neurological deficits.…”
Section: Discussionmentioning
confidence: 63%
“…It is also reported that posterior fixation of such degenerative tissue would reduce repetitive mechanical stimulation, thereby inhibiting stress on the spinal cord and reducing the inflammation which had produced the degenerative lesions. 9 10 Similar to degenerative cysts, retro-odontoid hypertrophy of soft tissue mass in a non rheumatoid patient with atlantoaxial subluxation has been reported to decrease after posterior fixation. 11 12 13 14 15 Nevertheless, the surgical procedure is appropriate for no neurologic symptoms and the small cystic mass.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have reported the correlation between the radiographic parameters and the development of SAS in patients with RA who underwent cervical intervention. 18 19 20 21 22 23 With regard to C1–C2 arthrodesis for AAS, several studies have mentioned that the optimal AA angle for C1–C2 fixation is ∼20 degrees. 23 24 Ishii et al reported that overcorrection of the atlantoaxial angle in C1–C2 arthrodesis is strongly correlated with the development of postoperative SAS.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Yoshida et al reported that decrease in range of motion in the O–C1 segments is a risk factor for postoperative SAS. 21 With regard to occipitocervical fusion, Matsunaga et al reported that in patients with RA, the position of fixation of the occipital bone and axis should be within the range of 0 to 30 degrees, considering the long-term effects on the middle and lower cervical vertebrae. 22 In the present study, the postoperative O–C2 angle was outside the range of 0–30 degrees in only two patients, who did not experience distal junctional disease.…”
Section: Discussionmentioning
confidence: 99%